PRODUKTIVITAS RUMPUT Panicum maximum CV. GREEN PANIC PADA BERBAGAI TARAF PEMUPUKAN KOTORAN SAPI DALAM KONDISI TERNAUNG DAN TANPA NAUNGAN - Wirawan, I Wayan; Suarna, I Wayan; Suryani, Ni Nyoman; Trisnadewi, Anak Agung Ayu Sri; Sumardani, Ni Luh Gede (Pastura; Vol 5 No 2 (2016): Pastura Vol. 5 No. 2 Tahun 2016DO - 10.24843/Pastura.2016.v05.i02.p12, 2017)
The research was carried out to study the effect of cattle manure fertilizer on produktivity of Panicum maximun Cv. Green Panic under shade and without shade conditions. The research used a block randomized design with split plot treatment arrangement and 3 replications. The main plot was shade and withaout shade and the sub plots were 4 level of cattle manure fertilizer (0, 10, 20, dan 30 t ha-1). The parameter of this research is grass height, number of leave, number of tillers, diameter of steam, dry wight of roots, forage and inflorescense production. The results of research showed that not interaction between shade and level cattle manure fertilizer on productivity Panicum maximun Cv. Green Panic. The use of shade 70 % decreasing of forage productions, number of tiller, diameter of steam, dry weight of roots and inflorescense production panicum grass (P<0,05). Increasing the use of cattle manur fertilizer increased of all parameter but not significantly. Key words: shade, cattle manur fertilizer, forage production, and Panicum maximum.